CORRECTION OF THE SYSTEMIC IMMUNITY HUMORAL COMPONENT PARAMETERS IN PATIENTS WITH GENERALIZED PERIODONTITIS - Savielieva, N.M.; Sokolova, I.I. (World of Medicine and Biology, 2019)
Dynamics of indicators of humoral arm of systemic immunity using complex therapy with the inclusion of immunomodulators in patients with chronic generalized periodontitis of I and II grades of development on giardiasis background was studied. It is established that the developed treatment regimen has a pronounced normalizing effect on the activity of humoral immunity. Under its influence, IgE and CIC levels in blood serum return to normal and the affinity of antimicrobial IgG antibodies increases. The obtained data give grounds to assert that the developed treatment regimen of complex therapy in patients with chronic generalized periodontitis of I and II grades of development on giardiasis background was more effective than conventional treatment.
Keywords: chronic generalized periodontitis; giardiasis; humoral immunity